2006
DOI: 10.1111/j.1365-2141.2005.05887.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of prospective screening of blood for invasive aspergillosis by polymerase chain reaction in febrile neutropenic recipients of haematopoietic stem cell transplants and patients with acute leukaemia

Abstract: Summary Guidelines for the use of polymerase chain reaction (PCR)‐based assays to aid the diagnosis of invasive aspergillosis (IA) in high‐risk haematology patients have not been formulated. We prospectively evaluated a nested PCR assay to detect Aspergillus in blood during 95 febrile neutropenic episodes, in patients with haematological malignancy and haematopoietic stem cell transplant (HSCT) recipients. PCR results were correlated with the diagnostic classification of the 2002 European Organisation for Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
2
66
1
3
Order By: Relevance
“…15,17,34 No conclusions regarding multiple [15][16][17]34,35 In our study, we did not find that PCR tests for Aspergillus were useful in patients with proven or probable IA. Fungal PCR tests were performed within 2 weeks of diagnosis in six of nine patients with proven or probable IA, and only one patient had a positive PCR test.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…15,17,34 No conclusions regarding multiple [15][16][17]34,35 In our study, we did not find that PCR tests for Aspergillus were useful in patients with proven or probable IA. Fungal PCR tests were performed within 2 weeks of diagnosis in six of nine patients with proven or probable IA, and only one patient had a positive PCR test.…”
Section: Discussioncontrasting
confidence: 40%
“…Although the results have been variable, the authors of some of these reports have concluded that PCR contributes to establishment of the diagnosis of IFI. [15][16][17] It has also been reported that a positive PCR test precedes the clinical diagnosis of invasive aspergillosis (IA), by several days up to several weeks. 15,16 These findings raise the question of whether PCR-guided early antifungal treatment could reduce the incidence and mortality of IFI after HSCT, in an analogous way to the successful development of pre-emptive treatment of CMV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity and specificity of PCR of BAL fluid samples are estimated to be 67-100% and 55-95%, respectively [111], while for serum samples the sensitivity and specificity have been reported as 100% and 65-92%, respectively [111][112][113][114]. However, PCR is often associated with false-positive results, because it does not discriminate between colonisation and infection.…”
Section: Diagnosismentioning
confidence: 99%